On Σ_t^σ -closed classes of finite groups - Skiba, A. N.; Zhang, Chi (Ukrains’kyi Matematychnyi Zhurnal, 2018)
All analyzed groups are finite. Let σ = { σ_i| i I} be a partition of the set of all primes P. If n is an integer, then the symbol σ (n) denotes a set {σ_i| σ_i π (n) ot = }. Integers n and m are called σ -coprime if σ (n) σ (m) = . Let t > 1 be a natural number and let F be a class of groups. Then we say that F is Σ^σ_ t -closed provided F contains each group G with subgroups A_1, ... ,A_t F whose indices | G : A_1| ,..., | G : A_t| are pairwise σ -coprime. We study Σ_t^σ -closed classes of finite groups.